Clinical Facial Analysis Elements, Principles, and Techniques - Meneghini, Fabio (Springer, 2012)
This richly illustrated book presents a straightforward non-instrumental method of clinical facial analysis in preparation for aesthetic surgery, orthognathic surgery, and orthodontic treatments. The opening chapters discuss various practical aspects of facial examination and photography. The role of precise and standardized three-dimensional photographic documentation of the face is highlighted, and a lighting technique developed by the authors is presented. Analysis of different regions of the face and dentofacial deformities is then discussed in a series of detailed chapters. At the end of each of these chapters, multiple-choice checklists are included that will help the reader to perform step-by-step regional analysis. Further chapters consider the aging face and post-treatment follow-up. Exercises on clinical photography and analysis are provided, and advice and quotations from experts are also included. Important features of the book are its multidisciplinary approach and the emphasis placed on the relationship between different parts of the face. This second edition has been thoroughly updated and includes a new chapter on recording and documentation relating specifically to aesthetic facial surgery.